O “ser mulher” na sociedade capitalista contemporânea: determinantes para o acesso das trabalhadoras domésticas aos direitos da Previdência Social - Silva, Amanda Kelly Belo da (2012)
This dissertation analyzes the domestic labor and access to social security rights in Brazil, considering that the different forms of women entering the work space and priority targeting of women to the work of social reproduction as a result of the sexual division of labor has folded in their access to social security rights, based on the logic of insurance and directly related to employment and income in Brazil. Thus, we began to investigate how the fact of being female, being relegated to a subordinate interaction, domination and exploitation of men, determines the quality and precariousness of work done by a fee, considering the patriarchal gender relations in capitalist society and new configurations of the sexual division of labor after 1970, and their access to rights related to social security in a context of State counter-reformation. In this process, we aim specifically to investigate domestic workers, paid and salaried, by understanding that they experience a strong situation of exploitation, because they have the same rights as other rural and urban workers, but also because of the devaluation of the breeding work social performed primarily by women, poor working conditions and low levels of access to social security. For this, we performed literature searches, documentary and even semi-structured interviews with 10 housekeepers who receive monthly salaries on Capim Macio district in Natal / RN. Regarding the exposure of the chapters we chose initially present patriarchal gender relations, the achievement of women's rights at work and new configurations of the sexual division of labor after 1970, trying to understand if they were being kept the old forms of exploitation or now if it would determine on a new basis. Then we analyze the construction of rights in Brazil, Social Security, as well as provide settings in contemporary social welfare in the context of dismantling of rights won. Finally, we analyze the formalization of the rights of domestic workers, their profile, their forms of participation in paid domestic work, their working conditions of access to pension rights, as well as their understanding of gender relations and domestic work.